Ichthyological diversity of the Mayapo stream, Peruvian Amazon - Armas Loarte, Maricell (2021)
The ichthyological diversity of the Mayapo stream is described based on material from the Ichthyological Collection of the Natural History Museum of the Universidad Nacional Mayor de San Marcos (UNMSM). We analysed material from 30 sample points of the Mayapo stream and tributaries, collected in 2005, 2009, and 2012. The points were located between 256 and 557 m of altitude. A total of 60 species grouped in 39 genera, 16 families, and four orders were identified. The Characiformes and Siluriformes orders including the Characidae and Loricariidae families were the most representative groups. We concluded that total ichthyological diversity in Mayapo stream and tributaries was moderated compared with previous studies in the Peruvian Amazon. Additionally, the taxonomic composition showed the common diversity pattern found in the Neotropical freshwaters and Peruvian Amazon. Finally, we also remark on fisheries species, migratory behaviours, and restricted distribution.